Collaborative and Problem Solving Instruments in Project-Based Physics Learning - Viyanti, Viyanti; Rosidin, Undang; Shintya, Rizki Eka (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to develop an assessment instrument that is able to measure collaboration and problem solving abilities in project-based physics learning that is valid, reliable and practical. This type of research is Research & Development by adapting 7 stages of development from Borg & Gall. Product expert validation was carried out to assess aspects of construction, substance and language, the results of expert validation of the assessment instrument were 87.85% with very valid criteria. As for the analysis of the results of field trials on 64 students using the Rasch model, it was obtained: (1) 21 questions about the collaboration ability instrument and 19 questions about the problem solving ability instrument were declared valid; (2) the reliability value of the collaborative and problem-solving ability assessment instrument is 0.97 and 0.89 (very good category); (3) the average value of the practicality test of the collaboration and solving ability assessment instrument is 81.21 (very high criteria).